(untitled) (Revista Apotheke, 2023)
Yawara! It is a manga created by Naoki Urasawa in 1985. This story marketed in comics tells the life story of Yawara, a high school student who, despite possessing great abilities and physical aptitudes to become an Olympic judo star, is torn between developing these potentialities or ignoring them to be included like any other young woman who follows the stereotyped and patriarchal canon of the society to which she belongs. In 1989 the plot was adapted into an anime television serial produced by Yomiuri TV and consisting of 124 episodes. Based on the plot of the television play, the first episode of the same is selected, to share in an artistic way through the research method based on the visual essay the feminist and anti-feminist messages that are transmitted to the consumer population of said resource. In this way, messages of empowerment are shared towards dissident women who break with gender issues linked to the development of professional sports careers, non-normative family structures and even ruptures of stereotyped behaviors with respect to normative and traditional genders. However, since the first episode of a series that evolves to totally feminist positions is analyzed, stereotyped messages related to the issue of romantic love are also extracted. These discourses must be made visible and critically reviewed. This is how an active and reflective consumption of the audiovisual product is attended.